2018
DOI: 10.3390/su10072232
|View full text |Cite
|
Sign up to set email alerts
|

Copula-Based Joint Probability Analysis of Compound Floods from Rainstorm and Typhoon Surge: A Case Study of Jiangsu Coastal Areas, China

Abstract: Coastal areas are vulnerable to floods caused by rainstorms and typhoons. It is necessary to ascertain the risk of floods caused by both of these extreme weather events. A conceptual risk model is proposed to evaluate the rainstorm risk, typhoon surge risk, and the compound risk in the coastal areas of Jiangsu Province during the period of 1960-2012. The results of the model show that the typhoon surge risk in the study region is greater than the rainstorm risk. Three Archimedean copulas were used to fit the j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A 10‐cm thick soil slope was successively loaded by two layers with 5‐cm thicknesses each time, and the surface of the lower soil layer was raked before the upper layer packed on top of it to ensure continuity between these two layers and achieve a uniform bulk density of 1.3 g/cm 3 . The soil slopes were then subjected to simulated rainfall using a sprinkler rainfall device with a fall height of 6 m. The maximum value of 1‐day average area rainfall in the coastal areas of Jiangsu was 54.8 mm for the period of 1960–2012 (Ai et al, 2018). The average hourly precipitation exceeded 23 mm in two coastal cities of Jiangsu (Dongtai and Nantong stations) during one severe convection precipitation event in June 2009 (Wang et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…A 10‐cm thick soil slope was successively loaded by two layers with 5‐cm thicknesses each time, and the surface of the lower soil layer was raked before the upper layer packed on top of it to ensure continuity between these two layers and achieve a uniform bulk density of 1.3 g/cm 3 . The soil slopes were then subjected to simulated rainfall using a sprinkler rainfall device with a fall height of 6 m. The maximum value of 1‐day average area rainfall in the coastal areas of Jiangsu was 54.8 mm for the period of 1960–2012 (Ai et al, 2018). The average hourly precipitation exceeded 23 mm in two coastal cities of Jiangsu (Dongtai and Nantong stations) during one severe convection precipitation event in June 2009 (Wang et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, research on the joint analysis of multiple hazard factors, based on data from station observations and numerical simulations, is gaining increasing prevalence. The primary research objectives of multivariate analysis include evaluating the correlation [54], dependence [55], encounter probability [56], combination design, and conditional probability [57] among multiple hazard factors. Correlation and dependence studies aim to quantify the interrelationships among these hazard factors.…”
Section: Statistical Modelsmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of copula functions in flood studies [28][29][30] and found that copula-based models provided a more accurate representation of the dependence structure between the variables, which was important in accurately assessing flood risk and designing appropriate management strategies. For example, Wang et al [31] proposed a copula simulation approach to developing a joint flood risk distribution of multi-reservoirs.…”
Section: Introductionmentioning
confidence: 99%